Problems of Legal Regulation of Combating Torture in Ukraine - Melnykova, Dariia (Journal of Legal Studies, 2022)
The relevance of this study is due to the lack of an effective mechanism to combat torture in Ukraine and an insufficiently effective system of prevention and protection against torture, which creates an atmosphere of impunity and leads to the spread of this phenomenon in Ukraine. The purpose of the article is to explore the problematic aspects of legal counteraction to torture in Ukraine and to suggest ways to improve the mechanism of legal counteraction to torture in Ukraine in the context of international standards. Thus, first of all, the article reveals the composition of the crime of torture and the specifics of responsibility for it in Ukraine. Then the paper characterizes the mechanism for ensuring legal counteraction to torture in Ukraine. The article also analyzes the main problems of legal counteraction to torture in Ukraine suggests ways to improve certain problems of legal counteraction to torture in Ukraine in the context of international standards.